Enteroparásitos y hemoparásitos en Trichechus inunguis Natterer, 1883, según áreas de cautividad en el Centro de Rescate Amazónico (CREA), Loreto-Perú - Macedo Tafur, Franco Ivan (2022)
The main threat that affects the Amazonian manatee is the contamination of rivers that facilitates the spread of parasitic diseases; therefore, the present study had the objective of determining the prevalence of enteroparasites and hemoparasites in Amazonian manatees of the Amazonian Rescue Center. Twenty-eight samples were obtained from 10 male and female manatees, including calves, juveniles and adults. Fecal samples were obtained by direct deposition and blood samples by direct extraction from the pectoral fin. For the detection of intestinal parasites, the direct method, Willis flotation and Kinyoun staining were used. For hemoparasites, direct observation of blood and thick drop with Giemsa staining was performed. The following Protozoa were recorded: Eimeria oocyst 1,2 and 3, Cyclospora, Cryptosporidium, Entamoeba cyst; and Helminths, as eggs of Ascaride 1 and 2, Oxyuridae, Ancylostomatidae, Nematode 1, 2 and 3, and a Trematode; with the highest prevalence being Eimeria (3) 100% and Cyclospora 80%. According to the areas of captivity, pre-release was the area with the highest number of enteroparasites recorded, as well as juveniles and the Fundo Furia facility, while in females and males their presence was indistinct. Statistically, these results were independent of the variables studied. No blood parasites were recorded in the samples obtained.